The Prevalence and Associated Death of Ventricular Arrhythmia and Sudden Cardiac Death in Hospitalized Patients With COVID-19: A Systematic Review and Meta-Analysis - Tan, Ziqi; Huang, Shan; Mei, Kaibo; Liu, Menglu; Ma, Jianyong; Jiang, Yuan; Zhu, Wengen; Yu, Peng; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2022)
Background Arrhythmia is a very common complication of coronavirus disease 2019 (COVID-19); however, the prevalence of ventricular arrhythmia and associated outcomes are not well-explored. Here, we conducted a systematic review and meta-analysis to determine the prevalence and associated death of ventricular arrhythmia and sudden cardiac death (SCD) in patients with COVID-19. Methods Databases of PubMed, Cochrane Library, Embase, and MdeRxiv were searched. Studies that could calculate the prevalence of ventricular arrhythmia/SCD during hospital admission or associated death in patients with COVID-19 were included. The study was registered with the PROSPERO (CRD42021271328). Results A total of 21 studies with 13,790 patients were included. The pooled prevalence of ventricular arrhythmia was 5% (95% CI: 4–6%), with a relatively high-SCD prevalence (1.8% in hospitalized COVID-19 and 10% in deceased cases of COVID-19). Subgroup analysis showed that ventricular arrhythmia was more common in patients with elevated cardiac troponin T [ES (effect size): 10%, 95% CI: −0.2 to 22%] and in European (ES: 20%, 95% CI: 11–29%) populations. Besides, ventricular arrhythmia was independently associated with an increased risk of death in patients with COVID-19 [odds ratio (OR) = 2.83; 95% CI: 1.78–4.51]. Conclusion Ventricular arrhythmia and SCD resulted as a common occurrence with a high prevalence in patients with COVID-19 admitted to the hospital. Furthermore, ventricular arrhythmia significantly contributed to an increased risk of death in hospitalized patients with COVID-19. Clinicians might be vigilant of ventricular arrhythmias for patients with COVID-19, especially for severe cases. Systematic Review Registration www.york.ac.uk/inst/crd, identifier: CRD42021271328.